2015
DOI: 10.1177/0886260515572473
|View full text |Cite
|
Sign up to set email alerts
|

Are College Students’ Assessments of Threat Shaped by the Dangers of Their Childhood Environment?

Abstract: Humans internalize environmental cues of mortality risk at an early age, which influences subsequent risk perceptions and behavior. In this respect, an individual's current risk assessment may be viewed as an adaptive response to the dangers present within his or her early local environment. Here we examine the relationship between several variables indicating threat within an individual's early environment (e.g., prevalence of violent and property crimes, registered sex offenders) and their perception of crim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…However, there may be other individual 526 difference factors that underlie the relationship between PPFDM and fear of crime, and this 527 warrants further examination. Women feel more or less vulnerable to victimisation for a number of 528 stability of PPFDM into adulthood (e.g., Sherman et al 2015). For example, an interesting avenue for 530 future research would be to examine the development of PPFDM as a function of childhood 531 experiences of crime, heightened vulnerability, and limited protection.…”
Section: Discussion 461mentioning
confidence: 99%
“…However, there may be other individual 526 difference factors that underlie the relationship between PPFDM and fear of crime, and this 527 warrants further examination. Women feel more or less vulnerable to victimisation for a number of 528 stability of PPFDM into adulthood (e.g., Sherman et al 2015). For example, an interesting avenue for 530 future research would be to examine the development of PPFDM as a function of childhood 531 experiences of crime, heightened vulnerability, and limited protection.…”
Section: Discussion 461mentioning
confidence: 99%
“…In this case, it might be considered unethical to adjust perceptions, and instead it would be better to focus on tackling sources of extrinsic mortality risk and improving people's future prospects. Furthermore, information gathered during early life may alter perceptions of, or responses to, environments in adulthood (Frankenhuis & Weerth 2013; Placek & Quinlan 2012; Sherman et al 2015), in which case, understanding the interaction between early experience and current context will be extremely important.…”
Section: The Implications Of the Contextually Appropriate Response Pementioning
confidence: 99%
“…Previous research has found that exposure to crime in childhood influences current perceptions of crime (Sherman et al 2016), as well as a preference for aggressive-formidable long-term partners (Snyder et al 2011). In our first study, objective crime rates in childhood were unrelated to male friend preference.…”
Section: Discussionmentioning
confidence: 59%
“…The results presented here point at the importance of subjective perceptions of the environment as the most important determinant of evolutionarily sensible choices when selecting friends. Although danger in childhood environment is related to current perception of risk (Sherman et al 2016), the current, subjective fear of crime is more crucial. Women who have higher fear of crime (irrespective of their actual environment) have been found to prefer aggressive-formidable male partners (Ryder et al 2016).…”
Section: Discussionmentioning
confidence: 99%